Differential Contribution of Ca2+-Dependent Mechanisms to Hyperexcitability in Layer V Neurons of the Medial Entorhinal Cortex - Lin, Eric C.; Combe, Crescent L.; Gasparini, Sonia (Frontiers in Cellular Neuroscience, 2017)
Temporal lobe epilepsy is characterized by recurrent seizures in one or both temporal lobes of the brain; some in vitro models show that epileptiform discharges initiate in entorhinal layer V neurons and then spread into other areas of the temporal lobe. We previously found that, in the presence of GABAA receptor antagonists, stimulation of afferent fibers, terminating both at proximal and distal dendritic locations, initiated hyperexcitable bursts in layer V medial entorhinal neurons. We investigated the differential contribution of Ca2+-dependent mechanisms to the plateaus underlying these bursts at proximal and distal synapses. We found that the NMDA glutamatergic antagonist APV (50 µM) reduced both the area and duration of the bursts at both proximal and distal synapses by about half. The L-type Ca2+ channel blocker nimodipine (10 µM) and the R- and T-type Ca2+ channel blocker NiCl2 (200 µM) decreased the area of the bursts to a lesser extent; none of these effects appeared to be location-dependent. Remarkably, the perfusion of flufenamic acid (100 µM) to block Ca2+-activated non-selective cation currents mediated by TRP channels had a location-dependent effect, by abolishing burst firing and switching the suprathreshold response to a single action potential for proximal stimulation, but only minimally affecting the burst evoked by distal stimulation. A similar outcome was found when FFA was pressure-applied locally around the proximal dendrite of the recorded neurons and in the presence of a selective blocker of TRPM channels, 9-phenanthrol (100 µM), whereas a selective blocker of TRPC channels, SKF 96365, did not affect the bursts. These results indicate that different mechanisms might contribute to the initiation of hyperexcitability in layer V neurons at proximal and distal synapses and could shed light on the initiation of epileptiform activity in the entorhinal cortex.